Penerapan DGBL (Digital Game Based Learning) Dengan Penggunaan Kahoot! Terhadap Motivasi Belajar Siswa Dalam Pembelajaran Matematika - Rahman, Ratu Firdausi; Dewi Nur, Iyan Rosita; Mustika Sari, Rika Mulyati (Cetta: Jurnal Ilmu Pendidikan, 2025)
Innovations need to be made in mathematics learning to motivate students, especially in learning models. One thing that motivates and is interesting for students is gadget games, namely games. The appropriate learning model is DGBL (Digital Game Based Learning). The media used is the Kahoot! As an interactive medium for new experiences for students. This research aims to conduct a Literature Review related to the use of Kahoot! can motivate students to learn mathematics. The research method chosen in this research is the Literature Review method, namely data collection is carried out by reviewing all articles related to the objectives of this research. The research used in this research were 20 accredited national journal articles obtained from the Google Scholar database using the application. Publish or Perish and international journals indicated by Scopus with a publication period of 2014-2024. The results of the study on the use of Kahoot! as a learning medium helped mathematics learning, with an average pretest and posttest score of 82.04 <94.04. Based on this research, the Kahoot! Not only can it increase students' learning motivation, but in previous research, the Kahoot! can increase student activity, student interest, student involvement and student motivation in learning mathematics.